Tamoxifen acts on Trypanosoma cruzi sphingolipid pathway triggering an apoptotic death process - Landoni, Malena (2019)
Fil: Landoni, Malena. Universidad de Buenos Aires, FCEN, Departamento de Química Orgánica - CONICET; Argentina.